Optimization Study of Plasma Actuator Efficiency Used Different Polymers - Raghad Star Karim Abdullah (Scientific Trends, 2023)
This work is an experimental study for plasma actuators to get a maximum efficiency at the best operating conditions using several variables such as different electrodes materials, horizontal distances between the effective and ground electrodes, also two type of dielectric materials used like Poly methyl methacrylate (PMMA) and high density polyethylene (HDPE). The discharge plasma was produced by AC power supply source of 8 KHz frequency and applied voltages (3, 5, 7, 9) kV. The results show that, the efficiency have maximum value, up to 0.25, when the dielectric is PMMA, copper electrodes, applied voltage of 7kV, and 1mm dielectric thickness. It’s clear there was distinction efficiency up to 0.20 using aluminum electrodes of 2mm thickness for PMMA dielectric and 5kV as applied voltage. Also, most likely the efficiency decrease with the increasing horizontal distance between the two electrodes.
Keywords: Optimization, polymers, plasma actuator efficiency.